High-performance work practices and employee wellbeing: organizational identification as a mediator - Salin, Denise; Stride, Chris; Smith, Sofia; Santokhie, Stefan (Frontiers in Psychology, 2023)
The aim of this study was to examine how high-performance work practices affect engagement and workplace bullying, two different aspects of employee well-being. Furthermore, the study sought to examine the potential mediating role of organizational identification in these relationships. A two-wave survey study (n=213) was conducted among psychologists in Finland. The results showed that high-performance work practices (HPWPs) were positively associated with engagement and negatively associated with the risk of workplace bullying. Moreover, organizational identification acted as mediator of the HPWPs-engagement relationship, though alongside the significant indirect effect via organizational identification there was also a significant direct effect of HPWPs on engagement. The study adds knowledge to ongoing debates on whether HPWPs support or undermine employee well-being. In particular, it extends our understanding of the association between HPWPs and relationship well-being, a topic that has so far received scant attention. Furthermore, the study advances our understanding of explanatory mechanisms in the HPWPs-engagement relationship and points to the importance of organizational identification for explaining why HPWPs lead to higher engagement.